Relative prevalence of Mycobacterium marinum in fish collected from aquaria and natural freshwaters in central Europe - Slany, M; Makovcova, J; Jezek, P; Bodnarova, M; Pavlik, I (Journal of fish diseases, 2014)
A survey was carried out on occurrence of Mycobacterium marinum in fish kept in aquaria and those living in their natural environment. Species-specific qPCR targeting the erp and IS2404 genes together with the conventional culture method were used. The analysis of 72 ornamental fish (n = 216 samples: gills, muscle and intestine) collected from aquaria revealed the presence of M. marinum in 30 individuals (41.7%) of whom 17 (23.6%) were later culture positive. Culture-independent detection revealed the presence of M. marinum in 16 of 83 environmental samples (19.3%) collected in aquaria. The presence of viable M. marinum cells was later confirmed in 5 samples (6.0%). No qPCR or culture positivity was observed when 123 groundwater fish and their corresponding environmental samples (n = 142) were analysed.
Keywords: molecular diagnostics; nemoci ryb; Gills; zvířata v ZOO; střeva; ryby; Fish Diseases; Sequence Analysis, DNA; prevalence; Intestines; Molecular Sequence Data; molekulární sekvence - údaje; RNA ribozomální 16S; Multiplex Polymerase Chain Reaction; žábry; zvířata; Colony Count, Microbial; Europe; bakteriální proteiny; multiplexová polymerázová řetězová reakce; RNA, Ribosomal, 16S; sladká voda; sekvenční analýza DNA; kosterní svaly; Fishes; Animals, Zoo; Fresh Water; Muscle, Skeletal; počet mikrobiálních kolonií; Czech Republic; atypické mykobakteriální infekce; fish mycobacteriosis; Bacterial Proteins; ecology; Prevalence; Animals; Česká republika; Mycobacterium marinum; Mycobacterium Infections, Nontuberculous; Evropa